Current opinions on mitophagy in fungi. Issue 3 (4th March 2023) - Shen, Zi-Fang; Li, Lin; Zhu, Xue-Ming; Liu, Xiao-Hong; Klionsky, Daniel J.; Lin, Fu-Cheng
ABSTRACT: Mitophagy, as one of the most important cellular processes to ensure quality control of mitochondria, aims at transporting damaged, aging, dysfunctional or excess mitochondria to vacuoles (plants and fungi) or lysosomes (mammals) for degradation and recycling. The normal functioning of mitophagy is critical for cellular homeostasis from yeasts to humans. Although the role of mitophagy has been well studied in mammalian cells and in certain model organisms, especially the budding yeast Saccharomyces cerevisiae, our understanding of its significance in other fungi, particularly in pathogenic filamentous fungi, is still at the preliminary stage. Recent studies have shown that mitophagy plays a vital role in spore production, vegetative growth and virulence of pathogenic fungi, which are very different from its roles in mammal and yeast. In this review, we summarize the functions of mitophagy for mitochondrial quality and quantity control, fungal growth and pathogenesis that have been reported in the field of molecular biology over the past two decades. These findings may help researchers and readers to better understand the multiple functions of mitophagy and provide new perspectives for the study of mitophagy in fungal pathogenesis. Abbreviations: AIM/LIR: Atg8-family interacting motif/LC3-interacting region; BAR: Bin–Amphiphysin–Rvs; BNIP3: BCL2 interacting protein 3; CK2: casein kinase 2; Cvt: cytoplasm-to-vacuole targeting; ER: endoplasmic reticulum; IMM: inner mitochondrial membrane; mETC: mitochondrial electron transport chain; OMM: outer mitochondrial membrane; OPTN: optineurin; PAS: phagophore assembly site; PD: Parkinson disease; PE: phosphatidylethanolamine; PHB2: prohibitin 2; PX: Phox homology; ROS, reactive oxygen species; TM: transmembrane.